Studies on Early Modern Aristotelianism. - Blum, Paul Richard (History of science and medicine library. Scientific and learned cultures and their institutions., 2012)
In Studies in Early Modern Aristotelianism Paul Richard Blum shows the Aristotelian profile of modern philosophy. Philosophy, sciences mathematics, metaphysics and theology under Jesuit leadership mark the difference of subject-centered modernity from 'teachable' school philosophy.